Energy level structure of Er3+. (February 2015) - Radžiūtė, L.; Gaigalas, G.; Kato, D.; Jönsson, P.; Rynkun, P.; Kučas, S.; Jonauskas, V.; Matulianec, R.
Abstract: Atomic energy levels and E2 and M1 transition rates are reported for the [Xe]4 f 11 ground configuration in Er 3+ from relativistic multiconfiguration Dirac–Hartree–Fock and configuration interaction calculations. The Breit transverse interaction and leading QED effects are included as perturbations. Different strategies for describing electron correlation effects are tested and evaluated. The calculated energy levels are compared with experiment and results from semi-empirical methods. Abstract : Highlights: 12 lowest levels of ground configuration for Er 3+ were calculated. E2 and M1 transition rates are reported for the ground configuration. Different strategies to include correlation effects are presented. The calculations are based on MCDHF and RCI methods.